La teoría del reconocimiento de Axel Honneth: un bosquejo moral de las formas de menosprecio social (2021)
This article establishes the conceptual criteria that allow Honneth to elucidate the idea of reification as a forgetfulness of recognition manifested in forms of contempt that, by revealing the subjection of individuals to situations of violence, dispossession of rights, and dishonor, lead to the need to undertake a struggle for recognition that, framed within normative moral horizons, entails the praxis of love, law, and solidarity as essential spheres to achieve human resignification.